Does slaughter age affect amino acids and fatty acids profiles and health and nutritional values of male and female ROSS 308 broiler chicken breast muscle? - Suliman, Gamaleldin M.; Al-Owaimer, Abdullah N.; Swelum, Ayman A.; Alhotan, Rashed; Qaid, Mohammed M.; Azzam, Mahmoud M.; Hussein, Elsayed O.S. (Poultry science, 2023)
Chemical composition, amino acids (AAs), and fatty acid (FAs) profiles, and health and nutrition values of breast muscle of ROSS 308 broiler chickens were studied after being slaughtered at 28, 35, 42, and 49 d of age (n = 126 males and 126 females/slaughter age). The slaughter age significantly affected some AAs levels including glutamic acid, valine, isoleucine, histidine, and leucine, and some FAs level including capric acid, tetradecanoic acid, eicosanoic acid, total saturated fatty acids, 9-pentadecenoic acid, hexadecatetraenoic acid, α-linolenic acid, stearidonic acid, linoleic acid, dihomo-γ-linolenic acid, arachidonic acid, adrenic acid, omega 6, sum polyunsaturated fatty acids (Ʃ PUFAs), and unsaturation index. Subsequently, the slaughter age significantly affected some health indexes including the n-6/n-3 ratio, thrombogenic index, hypocholesterolemic/hypercholesterolemic ratio, and health-promoting index. Valine, leucine, isoleucine, histidine, and glutamic acid levels increased with increasing slaughter age until 35 d of age and then decreased with increasing slaughter age until 49 d of age. Moreover, the health indices of fatty acids were best at slaughter age of 35 d, followed by 49 d, and the lowest health-promoting indices were at 42 d, followed by 28 d. The sex did not affect (P ˃ 0.05) all the evaluating parameters including chemical composition, amino acid and fatty acid profiles, and related health indices. There was no significant interaction effect between sex and slaughter age in all evaluating parameters except in stearidonic acid level. In conclusion, amino acids and fatty acids profiles and health and nutritional values of male and female ROSS 308 broiler chicken breast muscle can be affected by slaughter age. The study provides valuable insights into the nutritional value of meat, including its composition, amino acid, and fatty acid profiles, and associated health indices, for both male and female fast-growing ROSS 308 broiler chickens, as the slaughter age increases.